2009
DOI: 10.3109/19401730903176896
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among three newHemibarbusmitogenome sequences belonging to the subfamily Gobioninae (Teleostei, Cypriniformes, and Cyprinidae)

Abstract: Our findings are congruent with the previous taxonomic appraisal based on morphological analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…Within the latter group, there is a clear split into two lineages: one with Gobio and Romanogobio (the only two gudgeon genera with species native to Europe), and possibly Mesogobio; and the other with Abbottina, Biwia, Gobiobotia, Huigobio, Microphysogobio, Platysmacheilus, Pseudogobio, Saurogobio, and Xenophysogobio. The results presented herein match those from Yang et al (2006), Kim et al (2009), andLiu et al (2010), the previous molecular studies focusing on gobionine relationships. The distribution of specialized swim bladders indicates that that feature has evolved independently more than once within the subfamily.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Within the latter group, there is a clear split into two lineages: one with Gobio and Romanogobio (the only two gudgeon genera with species native to Europe), and possibly Mesogobio; and the other with Abbottina, Biwia, Gobiobotia, Huigobio, Microphysogobio, Platysmacheilus, Pseudogobio, Saurogobio, and Xenophysogobio. The results presented herein match those from Yang et al (2006), Kim et al (2009), andLiu et al (2010), the previous molecular studies focusing on gobionine relationships. The distribution of specialized swim bladders indicates that that feature has evolved independently more than once within the subfamily.…”
Section: Discussionsupporting
confidence: 79%
“…Kottelat, 2006;Bogutskaya et al, 2008). This would disagree with Kim et al (2009), who found H. barbus and H. labeo as sister taxa, though they were unable to examine H. maculatus, which we found as the sister species of H. labeo ( Figs. 1 and 2).…”
Section: Hemibarbus-squalidus Groupcontrasting
confidence: 55%
See 2 more Smart Citations
“…The mitogenome of H. labeo BML shows more closer relationship with other Hemibarbus fishes including H. labeo (Kim et al. 2009 ), H. barbus , H. maculatus , H. medius , H. umbrifer , H. mylodon , and H. longirostris. These results showed that, the mitogenome sequence can provide useful information in the taxonomy and conservation biology studies of H. labeo and other fish species.…”
mentioning
confidence: 86%